At Home in Renaissance Bruges Connecting Objects, People and Domestic Spaces in a Sixteenth-Century City - De Groot, Julie (Leuven University Press, 2022)
How did citizens in Bruges create a home? What did an ordinary domestic interior look like in the sixteenth century? And more importantly: how does one study the domestic culture of bygone times by analysing documents such as probate inventories? These questions seem straightforward, yet few endeavours are more challenging than reconstructing a sixteenth-century domestic reality from written sources. This book takes full advantage of the inventory as a source and convincingly frames household objects in their original context of use. Meticulously connecting objects, people and domestic spaces, the book introduces the reader to the rich material world of Bruges citizens in the Renaissance, their sensory engagement, their religious practice, the daily activities of men and women, and other social factors. By weaving insights from material culture studies with urban history, At Home in Renaissance Bruges offers an appealing and holistic mixture of in-depth socio-economic, cultural and material analysis. In its approach the book goes beyond heavy-handed theories and stereotypes about the exquisite taste of aristocratic elites, focusing instead on the domestic materiality of Bruges' middling groups. Evocatively illustrated with contemporary paintings and images of furniture and textiles from Bruges and beyond, this monograph shows a nuanced picture of domestic materiality in a remarkable European city.